Genome Sequence of Type Strain Bacillus decisifrondis E5HC-32(T) (DSM 11725(T)), Isolated from Soil Underlying the Decaying Leaf Litter of a Slash Pine Forest - Liu, Guo-hong (Genome Announc, 2015)
Bacillus decisifrondis E5HC-32(T) (DSM 11725(T)) is a Gram-positive, subterminal spherical spore-forming, strictly aerobic bacterium. Here, we report the 5,613,728-bp genome sequence of B. decisifrondis E5HC-32(T), which is the first genome information of this species and will provide useful information for genomic taxonomy and phylogenomics of Bacillus-like bacteria.